Rádio Galena : uma ferramenta pedagógica para discutir o transporte de energia através de ondas eletromagnéticas - Silva, José Arimathéia Alves da (2020)
This work is about a construction and application of a crystal radio as an educational product. The product contributes to the teaching of electromagnetic wave energy, having as fundamentals the Meaningful Learning of David Ausubel. In this approach, it was possible to discuss the historical context and the operation of the radio. The educational product was applied to students who attend the third year of the High School in the public school Irmã Diva Pimentel, in Barra do Garças-MT, Brazil. For this purpose, beyond the radio prototype, several didactic resources were used, like as PowerPoint slides, virtual simulations, the computer lab, problem situations and other activities. Since learning evidences have been noticed throughout the application of the educational product to the students, it is possible to consider that the work has been well succeed.